PELAKSANAAN PEMBELAJARAN TEKS EKSPOSISI PADA SISWA SMA NEGERI 1 SUBAH KABUPATEN SAMBAS TAHUN AJARAN 2018/2019 - Suriana Suriana; Ahadi Sulissusiawan; Syambasril Syambasril (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe reseach was motivated by a good exposition text learning result. It is important to know how the learning process is implemented by the teacher and the student in the learning process. The exposition text is important to be learned because besides givin knowledge about language fearures of exposition text, it also gives ecperiences about life through different point of views. The method of the research is descriptive method in a qualitative research. Te data of this research is exposition text learning to X MIA of SMA N 1 Subah. the data sources are the teacher an the students. The data is collected directly and indirectly. The tool of data collecting is the researcher herself as the main instrument. The teacher has applied the pre and post activity in the learning process. The teacher has checked the students’ presece, did the apperception, and concluded what has achieved  in the learning process. The teacher has implementtion the asking skill by deliver some questions to the students related to the materials. The teacher also asked some humorous questions in order to not make the students get nevous. The teacher has implementation te single teaching and hold a small discussions by grouping. But, the teacher still needs to improve her basic skill in classs management, create a various teaching method, an small discussion group management skill. The scoring is based on scoring rubric applied by teacher and result achieved by the students in the learning the exposition text is above average.Keywords: the learning Implementation, writing skills, exposition text.